Kantorovich-Stancu type Lototsky-Chlodowsky operators - Kutlu, Ş.; Karslı, H.; Taşdelen Yeşildal, F. (Carpathian Mathematical Publications, 2024)
In this study, we define Kantorovich-Stancu type Lototsky-Chlodowsky operators and obtain some approximation properties in weighted space of these operators. Furthermore, we prove Voronovskaja type results for the Kantorovich-Stancu type Lototsky-Chlodowsky operators.